Studi Perbandingan Penggunaan Pasta Gigi Detergen dan Non Detergen Terhadap Derajat Keasaman (pH) Saliva Anak Usia 10-12 Tahun di Madrasah Ibtidaiyah Al-Ma'arif Kebumen Kecamatan Banyubiru - Yustika, Agita Difa, drg. Lasmi Dewi Nurnaini, Sp.KGA, drg. Juwita Raditya Ningsih (2016)
Detergent toothpaste is a toothpaste which is containing detergent. Detergent usually add Sodium Lauryl Sulphate (SLS). SLS is a chemical that works by lowering the surface tension and cause the foam. SLS also has antibacterial and antimicrobial properties, thereby helping to reduce the acid environment of fermented bacteria that can directly increase the pH of saliva. The degree of acidity is a parameter of saliva to keep the balance and health of the oral cavity, which both are basic factors for caries progression and remineralization. High rates of caries prevalence is found for children aged 10-12 years old. The aim of this research is to determine the influence of detergent on toothpaste to salivary pH and to understand salivary pH, difference before and after brushing with a detergent toothpaste and non-detergent toothpaste for children aged 10-12 years old located in Madrasah Ibtidaiyah Al Ma'arif Kebumen District of Banyubiru. This type of research is a quasi-experimental design with one group pretest-posttest. The subject of study design the study are 32 children aged 10-12 years old are given two treatments, they are brushing teeth with detergent toothpaste and non-detergent toothpaste on different days. Salivary pH examination was taken before and after brushing teeth, then subjects were asked to collect saliva at a designated place. Salivary pH was measured using a digital pH meter SenseLine. The results show that there is significant difference in salivary pH before and after brushing teeth with detergent toothpaste and non-detergent toothpaste (p = 0.00), also there is significant differences in the increasing of the salivary pH between the use of detergent toothpaste and non-detergent toothpaste (p = 0.005). In conclusion detergent toothpaste is significant to increase salivary pH in children aged 10-12 years old. Key words : detergent toothpaste, non-detergent toothpaste, salivary pH